Word Class University Pada Pendidikan Islam - Zainal Panani; Sokip Sokip; Asrop Safi’i (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The purpose of writing this article is to find out word class university in Islamic education. This research uses a type of library research. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that policy is a series of actions/activities proposed by a person or a particular institution in a place to resolve obstacles and alternative implementation in order to achieve certain goals. The idea that policy involves behavior that has aims and objectives is an important part of the definition of policy, because after all policy must show what is actually done rather than what is merely proposed in some activity to solve a problem. The concept of a world class university. A world-class university is born with self-development and selfless efforts to meet universal standards. World class university is characterized by; firstly, the lecturers' works are widely used as references by many researchers, lecturers and students throughout the world. secondly, the ability to communicate in international languages, such as English and Arabic. Third, the research findings have an impact on world change. Fourth, all public information related to universities can be accessed by many people throughout the world, and Fifth, these universities have become places of study and research for students from various countries.